Productivity duration among farmers in semi arid regions in Zimbabwe: 2022 International Conference On Multidisciplinary Research (MyRes) 8-9 December 2022 The Ravenala Attitude Hotel, Turtle Bay, Balaclava, Mauritius - Sanderson Abel; Julius Mukarati; Pierre Le Roux; Tendai Maparara; Nzwirashe Magomana (Society for Research and Knowledge Management, 2023)
This paper applied the concept of survival analysis to estimate productivity duration among A1farmers in Zimbabwe and to identify the main factors influencing the probability of productivity.The Cox hazard model and the Weibull parametric model were applied in this study to analyse farmer productivity and a sample of 176 randomly selected farmers and a questionnaire was administered to solicit information on the wages, education level and the level of government support in terms of input subsidies.The results showed that educated farmers are more likely to be productive and take lesser time to increase their productivity levels compared to less educated farmers.This then pointed to the fact that the government of Zimbabwe should have targeted the education of farmers first before embarking on resettling the A1 smallholder farmers and this can also be considered in future land reforms. The study recommended that there be farmer education initiatives to speed up their graduation from survivor to hazard farmers.